Characterization of the “gut microbiota-immunity axis” and microbial lipid metabolites in atrophic and potential celiac disease - Ricci, Federica; Russo, Edda; Renzi, Daniela; Baldi, Simone; Nannini, Giulia; Lami, Gabriele; Menicatti, Marta; Pallecchi, Marco; Bartolucci, Gianluca; Niccolai, Elena; Cerboneschi, Matteo; Smeazzetto, Serena; et al. (Frontiers in Microbiology, 2022)
Introduction: Potential celiac disease (pCD) is characterized by genetic predisposition, positive anti-endomisial and anti-tissue transglutaminase antibodies, but a normal or almost normal jejunal mucosa as well as minor histological abnormalities without villous atrophy. To gain further insights into basic mechanisms involved in the development of intestinal villous atrophy, we evaluated and compared the microbial, lipid and immunological signatures of pCD and atrophic CD (aCD). Materials and Methods: This study included seventeen aCD patients, ten pCD patients and twelve healthy controls (HC). Serum samples from all participants were collected to analyze free fatty acids (FFAs). Duodenal mucosa samples of aCD and pCD patients were taken to evaluate histology, tissue microbiota composition and mucosal immune response. Results: We found no significant differences in the mucosa-associated microbiota composition of pCD and aCD patients. On the other hand, in pCD patients, the overall abundance of serum FFAs showed relevant and significant differences in comparison with aCD patients and HC. In detail, compared to HC, pCD patients displayed higher levels of propionic, butyric, valeric, 2-ethylhexanoic, tetradecanoic, hexadecanoic and octadecanoic acids. Instead aCD patients showed increased levels of propionic, isohexanoic and 2-ethylhexanoic acids, and a lower abundance of isovaleric and 2-methylbutyric acids as compared to HC. In addition, compared to aCD patients, pCD patients showed higher abundances of isobutyric and octadecanoic acid. Finally, the immunological analysis of duodenal biopsy revealed a lower percentage of CD4+ T lymphocytes in the pCD infiltrate compared to aCD patients. The functional characterization of T cells documented a pro-inflammatory immune response in both aCD and pCD patients, but the pCD patients showed higher percentages of Th0/Th17 and lower percentages of Th1/Th17. Conclusions: The results of the present study show, for the first time, that the duodenal microbiota of patients with pCD does not differ substantially from that of aCD, however, serum FFAs and local T cells displayed a distinctive profile between pCD, aCD and HC. In conclusion, our result may help shed new light on the “gut microbiota-immunity- axis”, lipid metabolites and duodenal immune response in overt CD and pCD patients, opening new paradigms in understanding the pathogenesis behind CD progression.